Comparison of Constitutional Theory and Practice between Indonesia, England and the United States - Harahap, Odi Alfazein; Virginia, Elissa; Limoya, Muhammad Zhahab (CV. Rayyan Dwi Bharata, 2024)
Constitutional law has such a long history and has experienced many fundamental dynamics of change in the field of state administration. It is unavoidable, with the many changes that have occurred, it will certainly have an impact on the system and development of the Indonesian state administration which has undergone very substantive changes. With the amendment to the 1945 Constitution, of course it has an impact on Indonesian constitutional law, because state administration is a branch of legal science which has the main source of law, namely the Constitution. This paper discusses two things, namely: First, how is the development of the theory and practice of constitutional law in Indonesia. Second, how is the development of the theory and practice of constitutional law in England and the United States. The result of this discussion is that the Amendments to the 1945 Constitution have fundamentally changed the Indonesian constitutional system. Various fundamental weaknesses possessed by the 1945 Constitution have been perfected through four amendments. At the implementation level, the expected changes are still far from expectations. The administration of the state and government which aims to achieve a just and prosperous society is constrained by various factors. Bagir Manan believes that all the anomalies in state administration during the Reformation period were caused by four main things: It was not in line with the basic conception of the 1945 Constitution, Weaknesses stemmed from laws, especially organic laws, Social behavior, Political behavior. There are differences between the theory and practice of constitutional law in each country such as one of them. In modern times, the concept of rule of law in Continental Europe was developed by Immanuel Kant, Paul Laband, Julius Stahl, Fichte, and others using German terms, namely